Analisis Perbandingan Metode TAM dan Metode UTAUT 2 dalam Mengukur Kesuksesan Penerapan SIMRS pada Rumah Sakit Wijaya Kusuma DKT Purwokerto - Fiby Nur Afiana; Pungkas Subarkah; A. Kholil Hidayat (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
Guidelines regarding the development of health services by the community indirectly require the management and executors of health services to provide services in an optimal and professional manner. With the help of information systems, it is expected to help management to achieve improved health services. This study aims to analyze the success of the application of the Hospital Management Information System (SIMRS), especially the medical record information system applied at Wijaya Kusuma Hospital, DKT Purwokerto. The TAM and UTAUT 2 methods are used by several researchers to measure the success of the application of information systems based on the wishes of users / consumers in using information systems. The TAM method was developed to explain the behavior of information system users. Placing attitude factors and each user behavior with the construct. UTAUT 2 is a development of the previous method which aims to help companies / organizations to understand how the use of information technology in supporting company / organizational performance Comparison of the final results of both methods is done to determine the extent to which the success of information systems can be explained by the two analysis results. produced. The final result stated that a better method was used in the success of the hospital management information system at Wijaya Kusuma Hospital, DKT Purwokerto, namely the UTAUT 2 method because the UTAUT method was able to measure 2,109 while the TAM method only measured 1,782.